2014
DOI: 10.1542/peds.2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Anti–TNF-α Therapy May Cause Neonatal Neutropenia

Abstract: Although anti-tumor necrosis factor (anti-TNF) antibodies are associated with a clear risk of agranulocytosis in adults and are known to cross the placenta, monitoring of the absolute neutrophil count (ANC) in neonates born to mothers receiving these biological agents is not currently recommended. Here, we report on the first case series of 4 newborn patients with severe neutropenia born to mothers treated for ulcerative colitis with infliximab during pregnancy (including the third trimester). The newborns pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 23 publications
(27 reference statements)
0
40
0
3
Order By: Relevance
“…It has been mentioned that two patients with rheumatoid arthritis treated with an anti-TNF-α strategy developed neurological symptoms, including demyelination lesions [251]. Furthermore, it was shown that newborns presented severe neutropenia after their mothers were treated with infliximab for ulcerative colitis during pregnancy [252].…”
Section: Targeting Tnf-α As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
“…It has been mentioned that two patients with rheumatoid arthritis treated with an anti-TNF-α strategy developed neurological symptoms, including demyelination lesions [251]. Furthermore, it was shown that newborns presented severe neutropenia after their mothers were treated with infliximab for ulcerative colitis during pregnancy [252].…”
Section: Targeting Tnf-α As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
“…In contrast to these reassuring data, a small case series describes the presence of transient severe neutropenia, subsequently complicated by skin infections, in four newborns after intrauterine exposure to infliximab (including the third trimester) [102]. Furthermore, in view of the death of a 4.5-month-old female infant who developed disseminated Bacillus CalmetteeGu erin (BCG) following BCG vaccination at 3 months of age, live vaccines should be considered with caution.…”
Section: Tnf Inhibitors and Pregnancymentioning
confidence: 99%
“…Although a few small follow-up studies4 9 suggest no serious adverse events in these children, one case report described a fatal case of disseminated bacille Calmette-Guérin infection in an infant exposed to IFX in utero, which showed that live attenuated vaccinations in children exposed to anti-TNF in utero may be associated with adverse outcome. In addition, a recent case series reported four infants exposed to IFX in utero with severe neutropenia at birth 10. Adverse outcomes in the newborn may be avoided by lowering perinatal anti-TNF serum levels in the infants by stopping anti-TNF treatment in the second trimester of pregnancy in women with IBD in remission 6.…”
Section: Introductionmentioning
confidence: 99%